Entrepreneurial Performance Construct, Its Dimensions, Measures and Issues - Subedi, Rita (Interdisciplinary Journal of Management and Social Sciences, 2021)
Entrepreneurial performance is a construct evolved from organizational theory and strategic management. It is extensively researched and discussed to define venture success or failure in entrepreneurship domain. However, there is lack of consensus between scholars to choose measures and data sources used to identify the behavior of entrepreneurial performance construct. Due to this they have been facing considerable difficulty to choose accurate and adequate performance measure which is critical to consistent results.  Present paper reviews existing literature focusing on entrepreneurial performance construct and its measurements. The purpose of this paper is to identify current position regarding the entrepreneurial performance construct and its measurements and issues. The existing literature related to measurements of entrepreneurial performance were reviewed. The results depicted that vast majority of the studies have considered unidimensional measures especially financial measures as core which covers mostly efficiency, profit and growth dimensions. Very few studies have considered operational, and stakeholder satisfaction dimensions. As like as measures, most of the studies, (more than 75 percent) were used primary data, very few studies were used secondary and triangulated data source. This leads the inaccuracy in results.